Artificial tongue based on carbon dots and a porphyrin derivative for pattern recognition of metal ions. Issue 1 (7th December 2022) - Liu, Xiaowei; Zhang, Zhiwei; Yan, Xuetao; Zhang, Xinying; Amblard, Francois; Chen, Yingying; Feng, Lingyan
Abstract : An array-based artificial tongue consisting of C-dots, TMPyP (porphyrin derivative) and a C-dot–TMPyP complex for the discrimination of different metal ions. Abstract : An artificial tongue for the discrimination of different metal ions based on fluorescent carbon dots (C-dots) and meso -tetrakis(4-( N -methylpyridiumyl))porphyrin (TMPyP) was developed in this manuscript. Fluorescence resonance energy transfer (FRET) between C-dots and TMPyP was applied for the sensor array consisting of C-dots, TMPyP and a C-dot–TMPyP complex. Fifteen metal ions have been effectively identified by the sensor array with different fingerprint-like patterns which were analyzed from the distinct fluorescence responses through principal component analysis (PCA) and hierarchical cluster analysis (HCA), providing a fast and efficient method for the detection of metal ions.